2015
DOI: 10.1007/s00345-015-1615-3
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic effect of tumour-infiltrating lymphocytic subpopulations in bladder cancer

Abstract: A high fraction of Tregs amongst CD3- and CD8-positive lymphocytes indicated a poor prognosis, thereby emphasising the important role that Tregs play in the suppression of the anti-tumour immune response. No single lymphocytic marker was significantly correlated with clinical outcomes, but high CD3 and CD8 infiltration showed trends towards better prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 21 publications
8
73
1
4
Order By: Relevance
“…An increased frequency of intratumoral FOXP3+ Tregs and inhibitory cytokines such as IL-10 and TGF-β was noted in bladder cancer patients compared to the healthy population [12, 2223, 39]. Interestingly, Treg frequencies and CD25 high and FOXP3- cells in peripheral blood were similar in different patient groups (control group, localized BCa, lymphogen metastatic BCa and distant metastatic BCa).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased frequency of intratumoral FOXP3+ Tregs and inhibitory cytokines such as IL-10 and TGF-β was noted in bladder cancer patients compared to the healthy population [12, 2223, 39]. Interestingly, Treg frequencies and CD25 high and FOXP3- cells in peripheral blood were similar in different patient groups (control group, localized BCa, lymphogen metastatic BCa and distant metastatic BCa).…”
Section: Discussionmentioning
confidence: 99%
“…In muscle-invasive bladder cancer, patients with FOXP3 expression in tumor cells had reduced long-term survival compared to patients with FOXP3-negative cancers [22]. Horn et al (2015) showed that a high FOXP3/CD8 ratio within invasive cancer tissue was an independent predictor of poor overall survival after cystectomy [23]. High numbers of CD68+ TAMs were associated with an advanced pT category and high-grade cancer [24], acting as an additional independent factor (CD68/CD3 ratio > 1) with a more than 7-fold higher risk of cancer-specific death on multivariate analysis [25].…”
Section: Discussionmentioning
confidence: 99%
“…In muscle-invasive bladder cancer, specifically, the presence of CD8 + tumor-infiltrating lymphocytes (TILs) (18) and a low ratio of FOXP3 to CD4 or CD8 expression on TILs (19) have been associated with improved disease-free and overall survival rates. In keeping with the work by Sharma et al (18), Cox proportional hazards (Cox PH) modeling for each immune gene signature across all tumors in TCGA BLCA data set The box plots denote the interquartile range (IQR), with the box representing Q1 to Q3, the line denoting Q2, and the whiskers extending an additional 1.5 times the IQR beyond Q1 and Q3.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, others have reported that CD3 + and CD8 + TILs are predictive of disease recurrence in patients with solitary low grade non-muscle invasive urothelial carcinoma and that CD4 + T cells are associated with a poor prognosis in this setting [257,258]. Another study showed that high CD3 + and CD8 + T cell infiltrates demonstrated trends towards better prognosis, but that high FOXP3/CD3 and FOXP3/CD8 ratios were correlated with poor outcomes [259]. Similar observations were made by Parodi and coworkers, who reported that the intra-tumoral T effector/T reg cell ratio in urothelial carcinoma patients with disease recurrence is invariably less than one, while it is always greater than one in patients without recurrence [260].…”
Section: Tils In Genitourinary Carcinomasmentioning
confidence: 99%